Translation Quality Assessment in the Subtitle of Idiomatic Expressions of Fast and Furious: Hobbs and Shaw Movie (Universitas Negeri Semarang, 2021)
Movie becomes the biggest industry in the world. Movie entertains audiences through the setting, plot, and also actor to give not only the quantity of the movie, but also to give the quality of the story. The existence of foreign movie has the biggest interest in entertainment aspect. Unfortunately, the use of foreign language in the movie appears any difficulties to understand the story. This study measures the translation quality and presents the descriptive qualitative approach to analyze the idiomatic expressions in the movie. It is found that many people still depend on the subtitle since the movie subtitles take a position in order to omit the gap between the source language and the target language. There are a lot subtitles which cannot be translated word-by-word and require a proper way to produce accurate and natural translation, especially in the term of idiomatic expressions which need quality assessment to be applied. The quality assessment of this idiomatic expression in Fast and Furious: Hobbs and Shaw movie has achieved all the scales of accuracy, readability, naturalness and clarity. It also shows the ideology of the translation based on the translator point of view in translating the idiomatic expressions of the subtitles.